The Effect of Learning Interest and Learning Motivation on Mathematics Learning Achievement - Sali Hasibuan, Alom; Yahfizham; Siregar, Tanti Jumaisyaroh (Yana Research, 2022)
This study aims to find out: How does interest in learning and learning motivation influence learning achievement in class VIII MTs Negeri 2 Padang Sidimpuan Academic Year 2018/2019. This research is quantitative research. The population of this study was students of class VIII MTsN 3 Medan Helvetia, which consisted of one class. Sampling used cluster random sampling with an average of 40 per class. In this thesis, the researcher used a questionnaire as a data collection instrument, totaling 35 statement items. And to analyze the data the researchers used univariate analysis (mean, median mode, and standard deviation), analysis prerequisite tests (normality and homogeneity tests) and hypothesis testing. The conclusion in this study is that there is an influence of interest in learning and learning motivation on learning achievement in class VIII MTs Negeri 2 Padang Sidimpuan Academic Year 2018/2019. This is based on the calculation of multiple correlation statistics obtained by Fcount > Ftable with the number 4.09 > 2.323